Effects of manual therapy on fear avoidance, kinesiophobia and pain catastrophizing in individuals with chronic musculoskeletal pain: Systematic review and meta-analysis - Kamonseki, Danilo Harudy; Christenson, Peter; Rezvanifar, S. Cyrus; Calixtre, Letícia Bojikian [UNESP] (Elsevier, 2021)
Objective: To systematically review the effectiveness of manual therapy on fear-avoidance, kinesiophobia, and pain catastrophizing in patients with chronic musculoskeletal pain. Literature search: Databases (Medline, EMBASE, CINAHL, PEDro, CENTRAL, Web of Science, and SCOPUS) were searched from inception up to March 2020. Study selection criteria: Two reviewers independently selected randomized controlled trials that investigated the effects of manual therapy associated or not with other interventions on fear-avoidance, kinesiophobia and pain catastrophizing in patients with chronic musculoskeletal pain. Data synthesis: Standardized Mean Differences (SMD) and 95% confidence interval (CI) were calculated using a random-effects inverse variance model for meta-analysis according to the outcome of interest, comparison group and follow-up period. The level of evidence was synthesized using GRADE. Results: Eleven studies were included with a total sample of 717 individuals. Manual therapy was not superior to no treatment on reducing fear-avoidance at short-term (low quality of evidence; SMD = −0.45, 95% CI -0.99 to 0.09), and intermediate-term (low quality of evidence; SMD = −0.48, 95% CI -1.0 to 0.04). Based on very-low quality of evidence, manual therapy was not better than other treatments (SMD = 0.10, 95% CI -0.56 to 0.77) on reducing fear-avoidance, kinesiophobia (SMD = −0.12, 95% CI -0.87 to 0.63) and pain catastrophizing (SMD = −0.16, 95% CI -0.48 to 0.17) at short-term. Conclusion: Manual therapy may not be superior to no treatment or other treatments on improving fear-avoidance, kinesiophobia and pain catastrophizing, based on very low or low quality of evidence. More studies are necessary to strengthen the evidence of effects of manual therapy on pain-related fear outcomes.
Keywords: Manipulative therapy; Mobilization; Pain-related fear; Physical therapy; Psychological factors